CREATING CUSTOMERSâ SATISFACTION THROUGH TOTAL QUALITY MANAGEMENT (TQM) IN S1 STUDENTS OF MANAGEMENT DEPARTMENT OF ECONOMICS FACULTY OF XYZ UNIVERSITY - Wijayanti, Ratna; Santoso, Aprih; Sukmadewi, Yudhitia Dyah (Economics and Business Solutions Journal, 2018)
The purpose of this study is to determine the efforts made by the S1 Management Study Program of Economics Faculty of XYZ University in applying Total Quality Management to increase customersâ / studentsâ satisfaction. This study used a descriptive qualitative method, which described the experiences of the informants, namely structural officials, lecturers, administrative staff and students on the efforts that have been given to increase studentsâ satisfaction. The results of this study indicate the application of 10 elements of Total Quality Management, namely focusing on customers, obsession on quality, scientific approach, long-term commitment, teamwork, continuous system improvement, education and training, controlled freedom, unity of purpose, and involvement and empowerment of employees have been carried out well and managed to meet the expectations of the students.